Strategi Strategi Menghadapi Tantangan Lingkungan Eksternal dalam Dunia Pendidikan - Hesti Kusumaningrum; Nurrohimah, Annisa Esa; Rintika Putri Pratama; Ahamad Bayhaqi Algifaro (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The world of education currently faces many dynamic external environmental challenges, such as changes in government policy, technological developments, labor market demands and socio- cultural changes. To face this challenge, educational institutions must develop adaptive and proactive strategies. This strategy includes curriculum innovation to adapt to current needs, increasing the capacity of teaching staff through continuous education and the application of technology in the learning process to increase access to skills and quality of education. Apart from that, collaboration with external parties such as industry and society is also important to create synergies that support the relevance and competitiveness of graduates. By taking a comprehensive and responsive approach, educational institutions can continue to grow and make meaningful contributions to ever-changing external challenges